High carnivore richness despite human pressure and prey depletion in the south-west of the Kavango–Zambezi Transfrontier Conservation Area - Stijn Verschueren; Tim Hofmann; Mikael Kakove; Hans Bauer; Bogdan Cristescu; Laurie Marker (Oryx)
Transfrontier conservation landscapes, such as the Kavango–Zambezi Transfrontier Conservation Area (KAZA TCA) in southern Africa, play a crucial role in preserving global biodiversity and promoting the sustainable development of local communities. However, resources to facilitate management could become scarce across large areas, leading to difficulties in obtaining baseline ecological information. Consequently, in the absence of sustainable management vast landscapes may experience loss of wildlife species, which could destabilize ecosystems. This effect is particularly significant if the loss involves top predators. Hence, understanding carnivore distributions is critical to informing management. We conducted a mammal survey in the Ondjou Conservancy in Namibia, an 8,729 km2 understudied area in the south-west of the KAZA TCA. We analysed camera-trapping data from a 2,304 km2 grid and identified high carnivore richness (18 species) despite widespread human activity and prey depletion. Using a multi-species occupancy framework we found that carnivore occurrence increased with increasing distance from the main village and with closer proximity to the Nyae Nyae Conservancy neighbouring the KAZA TCA, which has large and diverse carnivore populations. Carnivore occurrence was higher when local prey richness was high. The Ondjou Conservancy could function as an important buffer for the larger conservation network, yet rural communities in this area require support for fostering human–wildlife coexistence. Additionally, restoring the natural prey base will be critical to ensuring the long-term viability of carnivore populations in this and other human-impacted landscapes. With many remote areas of transfrontier conservation landscapes being understudied, our findings illustrate the conservation potential of such areas within large-scale conservation networks.